A linkage of welfare: industry, small business, and job creation - Suliswanto, Muhammad Sri Wahyudi; Firmansyah, Muhammad; Rofik, Mochamad; Kurniawan, Mahrus Lutfi Adi; Flejterski, Stanislaw (Jurnal Ekonomi & Studi Pembangunan, 2026)
This study aims to analyze the relationship between industry, small businesses, job creation, and welfare within an integrated analytical framework. This study uses a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, with primary data obtained from questionnaires distributed to 80 respondents in the industrial area of Gresik Regency, East Java, Indonesia. The results of this study indicate that industry significantly influences welfare, both directly and indirectly through small business development and job creation. In this case, small businesses act as a key mediating variable influencing industry's impact on job opportunities and improved welfare. The novelty of this study lies in the development of an empirical model that simultaneously integrates the roles of industry, small business development, job creation, and welfare within a single analytical framework, using small business and job creation as mediating variables. This research contributes to the development economics literature, particularly on inclusive growth. It provides a policy perspective on the importance of effective integration between industry and small businesses as a strategy for improving public welfare.